Rooftop Rainwater Harvesting for Domestic Water Demand and Supply Management and Designing of Optimum Rainwater Harvesting Structure in Imphal West District Manipur - Singh, L Kanta; Devi, S. Roma (Indian Journal of Hill Farming, 2017)
Rains are the main source of water and if rainwater is harvested, the scarcity of water can be eliminated. Manipur state was chosen for the study. The state lies at a latitude of 23°83’N – 25°68’N and a longitude of 93°03’E – 94°78’E and having a geographical area of 22,347 km². In Manipur many areas face serious threats to a safe and steady supply of water. To solve the problems of water supply and availability of quality water can be complex, but through rooftop rainwater harvesting, it can be one of the feasible solution to meet the domestic water demand. Rooftop rainwater harvesting is one of the methods of rainwater harvesting. It is a system of catching rainwater directly from where it falls. Runoff occurrence over the rooftop is collected for storage for future usage and this water is considered to be free from contamination. The total domestic water demand of Manipur was estimated at 84043520 m3 and domestic supply potential only from rooftop rainwater harvesting was estimated at 28134022 m3 which fulfil about 33.5% of total domestic water demand. The shortage which is about 66.5% can be through State Government’s water supply scheme, from the private sector and also from other sources like pond, river, lake, spring water, etc. January month was found to be the most water stress month with about 1.3% of water could be fulfilled through rooftop rainwater harvesting to the total domestic water demand. Whereas from May to September months rather peak monsoon months, rooftop rainwater harvesting could fulfilled more than 50% of the total domestic water demand. The average annual increase in domestic water demand from 2001 to 2026 was predicted at 1.09% and total increased in domestic water demand was predicted at 27.16%. So, there will be huge domestic water demand in coming future years.